Analisis Pengaruh Kualitas Pelayanan, Harga dan Kepuasan Konsumen terhadap Loyalitas Konsumen pada PT. KAI Commuter Jabodetabek (KCJ) (Studi Kasus pada Penumpang KRL Jakarta Kota-Bogor) - Rossanti, Endah Dwi; Muriyanti, Muriyanti (Cv. Syntax Corporation Indonesia, 2020)
The purpose of this research are to know and analysis how the effect of service quality, price and consumer satisfaction on the loyalty of consumer in PT. KAI Commuter Jabodetabek (KCJ) with case study on passanger of KRL Jakarta Kota – Bogor. The data collection technique by using questionnaire containing closed and open questions, to closed questions using Likert Scale. Sampling method used accidental sampling as many as 100 people. Data processing technique used is qualitative analysis and quantitative analysis. Based on the analysis, known linier regression equation is Y = 1,317 + 0,090X1 + 0,167X2 + 0,340X3. While the partial test result is the quality of service is not positive and significant impact on passenger loyalty, The price of ticket is positive and significant impact on passenger loyalty, and the last is satisfaction of passenger postive and significant impact on passenger loyalty. While the test result obtained that the coefficient of determination R2 is equal to 0,251. This suggests that at least 1 (one) of 3(three) independent variables can influence as many as 25% the dependent variable.